CO2 Adsorption and Desorption by Waste Ion-Exchange Resin–Based Activated Carbon on Fixed Bed - Wei, Mengqi; Zhao, Qiuyue (Frontiers in Energy Research, 2021)
The waste ion-exchange resin-based activated carbon (WIRAC) was utilized to CO2 adsorption. The effect of adsorption temperature, gas flow, CO2 concentration and adsorbent filling content on CO2 adsorption properties of WIRAC; the effect of desorption temperature and sweep gas flow on CO2 desorption performances of WIRAC were researched. In the adsorption process, with the increase of adsorption temperature, CO2 adsorption capacity and adsorption rate decrease; as the gas flow increases, CO2 adsorption capacity decreases but adsorption rate increases; with the increase of CO2 concentration and the adsorbent filling content, CO2 adsorption capacity and adsorption rate both increase. In the desorption process, the higher desorption temperature and the smaller sweep gas flow, the higher CO2 purity of product gas and the longer desorption time will be. In order to making sure the adsorbent be used efficiently and the higher CO2 concentration of product gas, the adsorption and desorption conditions should be made a suitable choice.